2022
DOI: 10.1007/s11356-021-18195-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the association between dust storms and COVID-19 infection rate in southwest Iran

Abstract: This study assesses a plausible correlation between a dust intrusion episode and a daily increase in COVID-19 cases. A surge in COVID-19 cases was observed a few days after a Middle East Dust (MED) event that peaked on 25 th April 2020 in southwest Iran. To investigate potential causal factors for the spike in number of cases, cross-correlations between daily combined aerosol optical depths (AODs) and confirmed cases were computed for Khuzestan, Iran. Additionally, atmospheric stability data time series were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 113 publications
0
7
0
Order By: Relevance
“…A wide array of meteorological factors including particulate matter, air pollution, and heat were identified as positively associated with the spread of COVID-19. Studies identified that reported on the relationship between meteorological parameters and COVID-19 spread in different regions of the world [ [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] ] are shown in Table 1 . The interplay among meteorological factors (air pollution, meteorological parameters, and climate change) ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide array of meteorological factors including particulate matter, air pollution, and heat were identified as positively associated with the spread of COVID-19. Studies identified that reported on the relationship between meteorological parameters and COVID-19 spread in different regions of the world [ [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] ] are shown in Table 1 . The interplay among meteorological factors (air pollution, meteorological parameters, and climate change) ...…”
Section: Resultsmentioning
confidence: 99%
“…Random Forest Analysis was used to evaluate the importance of parameters such as aerosol optical depth, temperature, pressure, humidity, and wind speed on the daily increase of COVID-19 infection The Middle East Dust incursion monitored by aerosol optical depth showed a statistically significant correlation with COVID-19 cases in some cities indicating the plausible role played by PM 10 in the spread of virus. [ 69 ] Fifteen (15) provinces in Turkey Concentrations of PM 2.5 , PM 10 , NO 2 , SO 2 , O 3 and COVID cases Data on air quality parameters were obtained from the Air Quality Open Data Platform. Meteorological data were obtained from the Ministry of Agriculture and Forestry.…”
Section: Resultsmentioning
confidence: 99%
“…The O 3 concentrations in 2020 increased by 12.2% compared to 2019 and declined by 3.9% in 2021. High levels of sand from the Middle Eastern dessert ( Broomandi et al, 2022 ) reached Southwestern Iran leading to high level of PM ( Khaniabadi et al, 2017a , 2019b ; Omidi Khaniabadi et al, 2019 ; Rashidi et al, 2022 ). The high PM levels led to lower solar radiation, and by consequence to lower O 3 formation ( Anbari et al, 2022 ; Grange et al, 2021 ; Higham et al, 2021 ; Siciliano et al, 2020 ), but also to destruction of O 3 on PM surface ( Sicard et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the city of Tehran, Iran, decreases of PM 10 up to 30% and PM 2.5 up to 103% were also reported. This is perhaps the largest decrease in PM 2.5 concentration reported in the literature (Broomandi et al 2022 ). In the case of the Chinese cities in Hubei Province, Wuhan, Jingmen, and Enshi, central China, the confinement measurement achieved reductions of PM 10 levels by up to 8.3% and of PM 2.5 up to 72% (Xu et al 2020 ).…”
Section: Introductionmentioning
confidence: 58%